2021
DOI: 10.1002/jsfa.11586
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic and myofibrillar phosphoproteins profile of beef M. longissimus thoracis with different pHu at different days postmortem

Abstract: BACKGROUND The abnormal ultimate pH (pHu) in postmortem muscles affect the meat quality and results in substantial economic losses. Dark, firm, and dry (DFD) meat linked with the higher postmortem pHu values and exhibited many quality issues such as dark color, tough texture and shorter shelf life. This research aimed to investigate the effect of protein phosphorylation on variations in beef pHu in order to explore the possible mechanisms underlying DFD meat formation. RESULTS Glycogen and lactate contents wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Higher myoglobin concentrations and inefficient mitochondria abundance revealed that animals predisposed to DFD-related issues had an oxidative metabolism that accelerated glycogen depletion as the degree of darkening in DFD meat increased [24,25]. It was also suggested that lower phosphorylation degree of sarcoplasmic proteins in intermediate (5.7 < pH < 6.09) and high pH groups (pH > 6.09) could have influenced the activity of certain metabolic enzymes associated with the development of DFD meat color [30]. Additional proteome studies also showed higher metabolic enzymatic activity in DFD meat with eight overabundant metabolic enzymes compared to normal-pH meat.…”
Section: Ultimate Phmentioning
confidence: 99%
“…Higher myoglobin concentrations and inefficient mitochondria abundance revealed that animals predisposed to DFD-related issues had an oxidative metabolism that accelerated glycogen depletion as the degree of darkening in DFD meat increased [24,25]. It was also suggested that lower phosphorylation degree of sarcoplasmic proteins in intermediate (5.7 < pH < 6.09) and high pH groups (pH > 6.09) could have influenced the activity of certain metabolic enzymes associated with the development of DFD meat color [30]. Additional proteome studies also showed higher metabolic enzymatic activity in DFD meat with eight overabundant metabolic enzymes compared to normal-pH meat.…”
Section: Ultimate Phmentioning
confidence: 99%
“…Rainy cold season dissipates body heat of the animals [9] and it has stressful effects during the transport or at meat processing plants. Apart from wet or cold weather, warm season has great concern with dark color of meat [34][35][36][37][38]. Knee et al [39] stated that during spring season, lambs show higher level of glycogen.…”
Section: Effect Of Climate Condition and Seasonmentioning
confidence: 99%
“…Beef aging is a technique widely used in the meat industry to enhance tenderness and produce a uniform product that is highly acceptable to the consumers, and therefore, extensive work has been done in this area [ 4 , 16 , 17 , 18 , 19 , 20 ]. Almost eight out of ten consumer decisions to repurchase meat are based on the tenderness of the meat, and for that reason, its better understanding is a significant challenge, mainly when the rate of aging varies among different species and different types of muscles [ 21 ].…”
Section: Introductionmentioning
confidence: 99%